Analisis Kandungan Gizi dan Daya Terima Cookies Substitusi Tepung Ikan Gabus dan Tepung Kacang Hijau - Eris Elvinta Lova; Miftahul Munir; Ahmad David Royyifi Arifin (SEHATMAS: Jurnal Ilmiah Kesehatan Masyarakat, 2024)
Chronic Energy Deficiency (CED) is a state of malnutrition caused by a lack of food intake for a long time impact to health problems, especially in pregnant women. Malnutrition for a long time in pregnant women impact on inhibiting the growth and development of the fetus. One of the supplementary feeding for pregnant women is cookies. This study aims to determine the nutritional content and acceptability of cookies substituting snakehead fish flour and mung bean flour as an alternative PMT for pregnant women with CED. This study used True Experimental with Completely Randomized Design (CRD), 4 levels of treatment and 6 times of replication. The treatment applied was the ratio of wheat flour : snakehead fish flour : mung bean flour at each P0 (100:0:0), P1 (80:10:10), P2 (70:15:15), P3 (60 :20:20). The results showed that there was an effect of increasing levels of protein, fat, ash, water, Fe, and decreasing levels of carbohydrates. There was a significant effect on the organoleptic quality as shown by the Kruskall-Wallis test (p <0.005) and continued with the Mann-Whitney follow-up test which showed that there were differences in all treatments. The conclusion of this study is that cookies substituted for snakehead fish flour and mung bean flour have an effect on nutritional value and organoleptic quality.